International sports organizations as diplomatic actors. The case of FIFA exerting influence on states - Kobierecki, Michał Marcin (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2019)
Contemporary diplomacy has evolved into a network involving various new actors, including international sports organizations. The article is dedicated to the issue of the sports diplomacy of international bodies which are in charge of international sporting competitions, particularly the International Federation of Association Football (FIFA), an organization that manages football on a global level. The research presented in this article is a case study dedicated to the issue of the influence of international sports organizations on the governments of sovereign states, specifically FIFA. The objective of the research is to investigate whether international sports organizations are able to make governments change their political decisions. The hypothesis that has been investigated states that international sports governing bodies are diplomatic actors capable of influencing states.

Współczesna dyplomacja przyjmuje coraz bardziej sieciową formę, co objawia się zaangażowaniem nowych aktorów, w tym międzynarodowych organizacji sportowych. Artykuł poświęcony jest zagadnieniu dyplomacji sportowej organizacji sportowych kontrolujących międzynarodową rywalizację sportową, na przykładzie Międzynarodowej Federacji Piłki Nożnej (FIFA). Badanie, którego dotyczy artykuł, stanowi studium przypadku poświęcone kwestii wywierania przez międzynarodową organizację sportową nacisku na rządy suwerennych państw, na przykładzie FIFA. Celem badania jest sprawdzenie czy organizacje sportowe są w stanie sprawić, aby rządy zmieniły swoje decyzje polityczne. Hipoteza, która została poddana weryfikacji zakłada, iż międzynarodowe organizacje sportowe są podmiotami dyplomatycznymi zdolnymi wpływać na państwa.
Międzynarodowe organizacje sportowe jako aktorzy dyplomatyczni. Przypadek FIFA wywierającej wpływ na państwa
Keywords: FIFA; sports diplomacy; diplomacy; international sports organizations; sport and politics; dyplomacja sportowa; dyplomacja; międzynarodowe organizacje sportowe; sport i polityka